Cases on Sampling in the Business Setting - Diyana, Kamarudin (Penerbit UMP, 2017)
Statistics from the Malaysian Communication and Multimedia Commission stated that out of every 100 household, 77.9 of those people are using broadband and 141.6 out of 100 people are using mobile phones. This shows that there is a huge market for the telecommunication industries, therefore, the telecommunication companies would have to be on their toes!